2021
DOI: 10.1021/acs.iecr.1c02579
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Olivine and Silica Sand with Potassium- or Silicon-Rich Agricultural Residues under Combustion, Steam Gasification, and CO2 Gasification

Abstract: Interactions between olivine or silica sand and potassium (K)-rich grape marc or silicon (Si)-rich wheat straw were studied in a fixed-bed reactor under combustion, steam, or a CO 2 gasification atmosphere. This study focused on the effects of atmosphere composition, feedstock, and bed material type on the thermochemical aspects of agglomeration. The agglomeration extent of grape marc with olivine as the bed material under air and steam atmospheres is significantly less than with silica sand. The presence of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 76 publications
(163 reference statements)
0
11
1
Order By: Relevance
“…The previous study of grape marc with olivine sand using a fixed-bed reactor showed that greater agglomeration is induced under the CO 2 gasification atmosphere compared to that under air and steam, which was associated with the carbonization of olivine. 60 However, the present investigation with the same feedstock and bed material indicated an inhabitation of the agglomeration process due to a restricted char conversion process under the CO 2 atmosphere compared with steam. Such difference revealed that CO 2 as the gasification agent can influence the reactivity of olivine sand as well as the extent of transformation of K contents in the char particles, both of which are required to drive the agglomeration process to occur.…”
Section: Under the Co 2 Gasification Conditionsmentioning
confidence: 53%
See 2 more Smart Citations
“…The previous study of grape marc with olivine sand using a fixed-bed reactor showed that greater agglomeration is induced under the CO 2 gasification atmosphere compared to that under air and steam, which was associated with the carbonization of olivine. 60 However, the present investigation with the same feedstock and bed material indicated an inhabitation of the agglomeration process due to a restricted char conversion process under the CO 2 atmosphere compared with steam. Such difference revealed that CO 2 as the gasification agent can influence the reactivity of olivine sand as well as the extent of transformation of K contents in the char particles, both of which are required to drive the agglomeration process to occur.…”
Section: Under the Co 2 Gasification Conditionsmentioning
confidence: 53%
“…Our previous study of similar feedstock showed that the wheat straw exhibits a higher degree of sintering than the grape marc under the same thermal conditions. 60 The presence of molten char particles with a large specific outer surface area can cause many bed particles to adhere rapidly and cause bed agglomeration, which can explain the rapid bed defluidization that occurred during the combustion of wheat straw. Figure 10b presents the magnified cross-sectional image of an agglomerate in the size range of 0.212−0.355 mm.…”
Section: Agglomeration Mechanism With Wheat Strawmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, for the marine macroalage, the steam atmosphere leads to more low-melting-point alkali silicates when compared with the air/N 2 atmosphere. Li et al also concluded that, for grape marc, the steam atmosphere retains more K in the agglomerates when compared with a CO 2 /N 2 (50% (v/v) CO 2 ) or air/N 2 (5% (v/v) O 2 ) atmospheres. For olivine sand, agglomerates are formed under the CO 2 /N 2 (50% (v/v) CO 2 ) atmosphere due to the formation of amorphous silica by the reaction between forsterite with CO 2 .…”
Section: Formation Of Agglomerates For Different Alkali Salts In Biomassmentioning
confidence: 99%
“…Biomass can be a sustainable feedstock for future energy security and sustainable development depending on its production, for example, mallee biomass in rural and regional Australia. , Direct combustion of biomass is a mature technology for power generation. Recycling nutrients in ashes from biomass combustion to the soil is important for the sustainable development of a biomass-based industry. This is possible for mallee biomass combustion because all the inorganic elements (nutrients and toxic trace elements, if any) are uptaken from the soil during tree growth.…”
Section: Introductionmentioning
confidence: 99%